Differential impairment of the sudomotor and nociceptor axon-reflex in diabetic peripheral neuropathy - Berghoff, Martin; Kilo, Sonja; Hilz, Max J.; Freeman, Roy (Muscle & nerve, 2006)
It is not known whether C‐fiber functional subclasses are differentially affected by diabetes mellitus or whether the patterns of C‐fiber dysfunction are different between type 1 and type 2 diabetes. We therefore examined efferent sympathetic sudomotor and primary afferent nociceptor C‐fiber function in diabetic patients. Acetylcholine (10%) was used to evoke C‐fiber (axon‐reflex)–mediated responses. The nociceptor (flare) response was measured using a laser Doppler device. The sudomotor response was quantified with silastic imprints. The nociceptor C‐fiber–mediated flare response was reduced in type 2 diabetic patients (P < 0.008) but was similar to controls in type 1 diabetic patients. The sympathetic C‐fiber–mediated responses, including sweat volume (P < 0.05) and the number of activated sweat glands (P = 0.003), were increased in patients with type 1 diabetes. There also was a trend toward a larger axon‐reflex sweat area in patients with type 1 diabetes (P = 0.09). No differences in these sweat responses were found in patients with type 2 diabetes compared to controls. These findings suggest that the functional abnormalities in diabetic peripheral neuropathy are not homogeneous and that C‐fiber subclasses are differentially affected in type 1 and 2 diabetes mellitus. Muscle Nerve, 2006